Socialization of Citizenship in Cultivating the Pancasila Spirit Among the Community: Sosialisasi Kewarganegaraan dalam Menumbuhkan Jiwa Pancasila di Kalangan Masyarakat - Natalia Louise; Dwi Andayani; Elisa Ananda Natalia; Sofiyan Matondang (ADI Publisher, 2025)
Pancasila, as the foundational ideology of Indonesia, plays a vital role in shaping the nation's character; however, public understanding of its values remains limited.This citizenship outreach program aims to cultivate the spirit of Pancasila by enhancing public awareness of national values through an educational approach. The program also engages students through the Raharja Enrichment Program (REP), an academic initiative that encourages student participation in community service as part of their learning experience. Using an Outcome-Based Education (OBE) approach, this qualitative study employed interviews and observations of community members involved in the program. Five key variables were examined: Citizenship Socialization, Citizenship Education, Social Environment, Legal Awareness, and the Spirit of Pancasila. The findings indicate that public understanding of Pancasila improved significantly following the outreach activities. Moreover, legal awareness serves as a moderating factor that strengthens the relationship between citizenship socialization and the practice of Pancasila values. Through REP involvement, the program not only benefits the community but also fosters student character development as active and responsible citizens. In conclusion, this program proves effective in promoting Pancasila awareness and provides meaningful learning experiences for students. Future initiatives should strengthen collaboration among academics, government, and local communities to broaden the program’s impact and sustainability.